The Effect of Store Atmosphere and Service Quality on Customer Satisfaction - Thalita, Viona Carissa; Surachman (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this research is to identify the effects of store atmosphere and service quality on the satisfaction of Sardo supermarket’s customers in Malang City. This explanatory study elucidates the causal relationship between its variables through hypothesis testing. Using non-probabilitysampling method and purposive sampling technique, 130 people with the minimum age of eighteen years who live in Malang City and have shopped in the supermarket more than once were selected as the respondents. The data of this study was harvested via Likert-scaled questionnaires. The research instruments were assessed using validity and reliability test, and the hypotheses were tested using F-test and t-test. All of the statistical processes were performed in SPSS 25. This study finds that store atmosphere and service quality significantly affect customer satisfaction. This research proves thatenhancement in store atmosphere and service quality is followed by advancements in customer satisfaction level.